UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN BENALU BATU (Begonia sp) TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli - Rikha Arliandini; Nur Mahdi; Ani Agustina (Jurnal Insan Farmasi Indonesia, 2023)
Empirically, begonia leaves are used as a treatment for cancer and ulcers.Â  contains chemical compounds of flavonoids, alkaloids, saponins, tannins and steroids. This study aims to determine the antibacterial activity of ethanol extract of begonia and its effective concentration against Escherichia coli and Staphylococcus aureus bacteria. Extraction with 96% ethanol extract using the maceration method. Phytochemical screening test, antibacterial test using various concentrations of 30%, 50%, 100%, positive control (ciprofloxacin) and negative control (aquadest steril) using the disk diffusion method. The results of the phytochemical screening of begonia extract contain alkaloids, flavonoids and tannins. The results of the antibacterial activity test for Staphylococcus aureus were obtained with an inhibitory zone concentration of 30%, namely 3.75 mm, 50%, namely 4.37 mm, and 100%, namely 4.87 mm. Meanwhile, Escherichia coli bacteria obtained a concentration of 30%, namely 4.37mm, 50%, namely 4.62 mm, and 100% is nm 4.75mm. The diameter of the inhibition zone for the positive control of ciprofloxacin against Staphylococcus aureus bacteria was 40.31mm and Escherichia coli was 44.12mm. The ethanol extract of begonia leaves can inhibit the growth of Staphylococcus aureus bacteria at a concentration of 100% is 4.87mm and Escherichia coli bacteria at a concentration of 100% is 4.75mm